발전국가론적 관점에서 본 새마을운동과 정부 역할 : 개도국 적용의 유용성 - 이미숙 (한국농촌경제연구원, 2013)
Since its inception in the early 1970s, Saemaul Undong(SMU) has played a pivotal role in bridging the economic growth gap between rural and urban Korea that eventually brought progress to the entire nation. SMU, a Korean community development movement, is not only recognized by the global community but also inscribed on the UNESCO Memory of the World Register. This study seeks to investigate success drivers of SMU’s promotion processes from a role of government perspective. The research also intends to discover and propose implications of rural development processes in less developed countries via SMU of the 1970s from the viewpoint of the development state theory of Asian countries by Chalmers Johnson and Alice Amsden. Effectual execution of SMU is derivative of harmonic balance between mobilization and participation of the actors involved; the focus of this paper is rather on the analysis of the role of government centering around institutional mechanism and political and administrative efforts of the state. The proposed Globalization Strategy of SMU negates the traditional ODA model of material and human resource-based aid for rural development; rather it suggests emphasis on the role of government to establish an effective and sustainable administrative system governed by policy makers in order to achieve villager participatory rural development.
Keywords: 발전국가론; 새마을운동; 정부역할; 농촌개발; 공적개발원조; development state theory; Saemaul Undong; government role; rural development; Official Development Assistance: ODA